2012
DOI: 10.4172/2157-7471.1000161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Some Botanicals and Entomopathogenic Fungi for the Control of Onion Thrips (Thrips tabaci L.) in West Showa, Ethiopia

Abstract: Onion thrips (Thrips tabaci L.) is one of the most important serious insect pests of onion (Allium cepa L.) cultivation in Ethiopia. The present study was conducted to evaluate some botanical extracts viz. Artemisia annua, Azadirachta indica, Bidens pilosa, Chrysanthemum cinerariaefolium, Cymbopogon citratus, Nicotiana tabacum, Nicotiana spp., (local var.,), Parthenium hysterophorous, Phytolacca dodecandra, Securidaca longepedunculata and two indigenous isolates of entomopathogenic fungi (EPF) viz. Beauveria b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 5 publications
(5 reference statements)
1
16
0
5
Order By: Relevance
“…This injury reduces the photosynthetic ability of the plant by destroying chlorophyll-rich leaf mesophyll (Lewis, 1973 and which may interfere with transportation of nutrients to the bulb (Kendall and Bjostad, 1990;Parrella and Lewis, 1997). In Ethiopia, T. tabaci is an important onion insect pest (Shiberu et al, 2013) that destroys onion fields, especially in the dry seasons. Onion bulb yield loses due to onion thrips reported ranged between 10 to 85% (Abate, 1985;Merene, 2005;Bekelle et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This injury reduces the photosynthetic ability of the plant by destroying chlorophyll-rich leaf mesophyll (Lewis, 1973 and which may interfere with transportation of nutrients to the bulb (Kendall and Bjostad, 1990;Parrella and Lewis, 1997). In Ethiopia, T. tabaci is an important onion insect pest (Shiberu et al, 2013) that destroys onion fields, especially in the dry seasons. Onion bulb yield loses due to onion thrips reported ranged between 10 to 85% (Abate, 1985;Merene, 2005;Bekelle et al, 2006).…”
mentioning
confidence: 99%
“…Several synthetic insecticides have been widely used to control onion thrips in the field (Mayer et al, 1987) and though effective in bringing down pest populations, these chemical insecticides are costly and unsafe to both humans and the environment (Nault et al, 2012;Jensen and Simko, 2001) particularly to smallholder farmers who fail to follow the practices of safe handling and application of pesticide. Moreover, as most smallholder famers may not afford the ever increasing costs of pesticides, alternative non-chemical insecticides, such as botanicals (Ayalew, 2005;Shiberu et al, 2013), are found to be the best option for smallholder vegetable production.…”
mentioning
confidence: 99%
“…Dodia et al [25] reported that Cymbopogon citrates had an effect on the onion thrips management. Shiberu et al [26] also mentioned that Cymbopogon citrates was reduced the population number of onion thrips at the rate of 10 g/liter of water. An overall performance of two consecutive sprays in two different locations against the population of cabbage aphid by insecticides gave as an average effect after third day of application.…”
Section: Effect Of Botanicals Against Cabbage Aphidmentioning
confidence: 99%
“…Alguns fungos entomopatogênicos têm sido relatados com eficácia sobre o controle de T. tabaci em bioensaios, como Beauveria bassiana (HEMALATHA et al, 2014), e Metharhizium anisopliae em ambiente protegido (POURIAN et al, 2011). Em pesquisa de campo, B. bassiana tem apresentado maior eficácia que M. anisopliae (SHIBERU et al, 2013).…”
unclassified
“…O nim, Azadirachta indica A. Juss (Meliaceae), é uma planta com efeito inseticida muito utilizada pelo baixo impacto ambiental (DEBASHRI & TAMAL, 2012). Os extratos de sementes de nim reduziram a incidência de T. tabaci quando administrados em doses entre 2,5% a 3% (SHIBERU et al, 2013).…”
unclassified